Prevalence of sudden cardiac death in dogs with atrial fibrillation. (9th November 2021) - Borgeat, Kieran; Pack, Matthew; Harris, Jo; Laver, Alex; Seo, Joonbum; Belachsen, Omri; Hannabuss, Joshua; Todd, Julie; Ferasin, Luca; Payne, Jessie Rose
Abstract: Background: Atrial fibrillation (AF) is associated with increased risk of sudden cardiac death (SCD) in humans, independent of secondary risk factors such as thrombogenic disorders. In dogs, SCD is described in a number of heart diseases, but an association between AF and SCD is unreported. Hypothesis: (a) A higher proportion of dogs with AF will experience SCD, and (b) SCD will be associated with complex ventricular arrhythmias. Animals: One‐hundred forty‐two dogs with AF, and 127 dogs without AF. Methods: Retrospective, multicenter, case‐control study. Dogs included in the AF group were compared to a control group of dogs in sinus rhythm, matched for echocardiographic diagnosis. Descriptive statistics were used to identify proportions of each group suffering SCD, compared using chi‐squared testing. Risk factors for SCD in dogs with AF were evaluated at the univariable and multivariable level using binary logistic regression. Significance was P  < .05. Results: A significantly higher proportion of dogs with AF suffered SCD than dogs in the control group (14.8% vs 5.5%; P  = .01). Younger age at diagnosis, larger left atrial size, and a history of syncope all were independent predictors of SCD in dogs with AF ( χ 2, 16.3; P  = .04). Conclusions and Clinical Importance: Atrial fibrillation was associated with a higher prevalence of SCD in dogs. A history of syncope may be a useful predictor of SCD risk.